Evaluation of three ELISA kits for the screening of colistin residue in porcine and poultry muscle according to the European guideline for the validation of screening methods. Issue 10 (2nd October 2020) - Gaudin, Valérie; Hédou, Céline; Rault, Annie; Verdon, Eric; Soumet, Christophe
ABSTRACT: Colistin is a polypeptide antibiotic mainly used in porcine and poultry to treat gastrointestinal infections. It has been included by the World Health Organisation (WHO) in the list of critically important human antibiotics of high priority for antimicrobial resistance since 2017. Therefore, it is necessary to develop specific and sensitive screening methods for this molecule. Screening for colistin with immunoassays is an interesting alternative to LC-MS/MS screening methods. The performance of three commercially available ELISA kits was evaluated in poultry and porcine muscles for the detection of colistin in regards to its European maximum residue limit (MRL) (150 µg/kg). The applicability of the three ELISA kits to the detection of colistin at or below the MRL in porcine and poultry muscles was demonstrated. The detection capabilities (CCβ) of two kits were or lower than or equal to the MRL (150 µg/kg). The lowest detection capability (30 µg/kg) was achieved with the third ELISA kit. The specificity of the three kits was very satisfactory (false positive rates 0%). The three kits are very specific for the detection of colistin (colistin A and B) and polymyxin B.